2006
DOI: 10.1303/aez.2006.515
|View full text |Cite
|
Sign up to set email alerts
|

Depth of pupation and survival of the Oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) pupae at selected soil moistures

Abstract: Estimates of pupation depth and survival of the Oriental fruit fly, Bactrocera dorsalis (Hendel), are important for optimizing soil control and for better understanding its natural mortality in the agricultural system of Guangzhou, China. Late third-instar larvae were placed in soils having relative moistures of 0-100% for pupation. No pupae were found on the surface at soil moistures of 0-70%. Instead, more than 50% of the larvae pupated on the surface at soil moistures of 80, 90, and 100%. Most of the larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 14 publications
7
48
1
Order By: Relevance
“…The range of pupation depths recorded in this study, 0-50 mm, is comparable to depths found by others, 5-40 mm, in laboratory tests using tropical tephritids (Dimou et al 2003;Hennessey 1994;Hou et al 2006;Jackson et al 1998;Tsitsipis and Papanicolaou 1979). The depths are also similar to those reported in the field for other tephritids, including Rhagoletis spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The range of pupation depths recorded in this study, 0-50 mm, is comparable to depths found by others, 5-40 mm, in laboratory tests using tropical tephritids (Dimou et al 2003;Hennessey 1994;Hou et al 2006;Jackson et al 1998;Tsitsipis and Papanicolaou 1979). The depths are also similar to those reported in the field for other tephritids, including Rhagoletis spp.…”
Section: Discussionsupporting
confidence: 89%
“…The authors suggested that the dense layer of blueberry roots probably impeded deeper pupation. In other studies, tropical tephritid flies, i.e., Anastrepha suspensa (Loew) and Bactrocera oleae (Gmelin), Caribbean and olive fruit flies, responded to increased moisture and soil density or compactness by pupating closer to the surface (Hennessey 1994; Tsitsipis and Papanicolaou 1979), and Bactrocera dorsalis (Hendel), Oriental fruit fly, pupated on the surface of saturated soil (Hou et al 2006). In other studies, however, pupation depth increased when soil or sand moisture levels were increased, i.e., Bactrocera spp.…”
Section: Introductionmentioning
confidence: 88%
“…SIT programs for some other tephritid pests, such as medflies, irradiate and ship pupae in sealed bags so that they experience hypoxic or anoxic conditions for 24-36h (FAO/IAEA/USDA, 2003), albeit at low temperatures (4°C). Like other tephritid fruit flies, caribflies pupate in the soil and their pupae are expected to regularly experience hypoxia or anoxia for several hours when inundated by rainfall (Hou et al, 2006;Montoya et al, 2008). This history of exposure to environmental hypoxia during the soil-bound immobile pupal stage may contribute to the anoxia tolerance in caribfly pupae, which are known to survive well even after 60h of anoxia (Benschoter et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality (LD 90 ) was 2.49 d for third instar B. dorsalis larvae in flooded conditions at 25 °C (Xie and Zhang 2007); however, no information for the pupae was available, so it was assumed that pupae would respond similarly to flooding like larvae. Bactrocera dorsalis pupae did not survive at soil moisture greater than 80% (Hou et al 2006), although the survival time in saturated soils is unknown. A study with Mediterranean fruit fly showed that survival under similar conditions were 4 and 3 days for larvae and pupae, respectively (Eskafi and Fernandez 1990).…”
Section: If T < T Min ; or T > T Max Thenmentioning
confidence: 96%